Spatio-temporal data mining in palaeogeographic data with a density-based clustering algorithm - Hemerich, Daiane (2014)
The usefulness of data mining and the process of Knowledge Discovery in Databases (KDD) has increased its importance as grows the volume of data stored in large repositories. A promising area for knowledge discovery concerns oil prospection, in which data used differ both from traditional and geographical data. In palaeogeographic data, temporal dimension is treated according to the geologic time scale, while the spatial dimension is related to georeferenced data, i.e., latitudes and longitudes on Earth s surface. This approach differs from that presented by spatio-temporal data mining algorithms found in literature, arising the need to evolve the existing ones to the context of this research. This work presents the development of a solution to employ a density-based spatio-temporal algorithm for mining palaeogeographic data on the Earth s surface. An evolved version of the ST-DBSCAN algorithm was implemented in Java language making use of Weka API, where improvements were carried out in order to allow the data mining algorithm to solve a variety of research problems identified. A set of experiments that validate the proposed implementations on the algorithm are presented in this work. The experiments show that the solution developed allow palaeogeographic data mining by applying appropriate formulas for calculating distances over the Earth s surface and, at the same time, treating the temporal dimension according to the geologic time scale